How US-made rules shape internet governance in China - Tusikov, Natasha (Internet policy review, 2019)
The United States is shaping Chinese internet governance by embedding US-preferred standards for the protection of intellectual property rights within Chinese platforms. As a result, the China-based Alibaba e-commerce giant has instituted US-drafted rules to deal with the sale of counterfeit goods. To explain this development, the article introduces the concept of compliance-plus regulation, which draws from regulatory theory and socio-legal studies to account for the state coercively pressuring one set of private actors (platforms) to regulate "voluntarily" on behalf of another set of private actors (rights holders). Drawing upon an analysis of documents from the US government, US industry, and Alibaba, the article finds that while economic pressure on Alibaba was a central factor, there are also common economic interests between Alibaba and US and European rights holders.